Trade-offs in thermal and mechanical properties of cellulose films from bacterial cellulose powder induced by ultrasonication duration - Dieter Rahmadiawan; Tio Baskara; Hairul Abral; Eni Sugiarti; Ahmad Novi Muslimin; Shih-Chen Shi; Thiago F. Santos; Imtiaz Ali Laghari (Universitas Negeri Padang, 2026)
Understanding the trade-offs between thermal and mechanical properties is crucial for optimizing the performance of cellulose films from bacterial cellulose powders (BCP). This study leverages ultrasonication as an eco-friendly method to enhance these properties in BCP-based films while investigating the consequences of varying ultrasonication durations. BCP was sonicated at 250 W for 15 and 30 minutes. Results demonstrated that increasing ultrasonication duration significantly improves tensile strength, toughness, and transparency. The 30-minute sonication yielded the most robust and transparent films, with the highest mechanical strength and toughness. Conversely, while a shorter sonication of 15 minutes slightly improved the thermal stability of the films, increasing Tmax from 317°C for non-sonicated films to 351°C, a longer duration of 30 minutes reduced Tmax to 323°C. This illustrates a clear trade-off between enhancing mechanical properties and maintaining thermal stability. The findings provide insights into a simple yet effective approach for producing environmentally friendly, non-wood-based BC films, emphasizing the need to balance both thermal and mechanical enhancements through controlled ultrasonication.